PS02.119: THE IMPACT OF RECEIVING ADJUVANT CHEMOTHERAPY ON SURVIVAL IN PATIENTS WITH LOCALLY ADVANCED ADENOCARCINOMA OF THE OESOPHAGUS. (14th September 2018) - Madhavan, Anantha; Phillips, Alex; Wyatt, Nicola; Boreham, Charlotte; Navidi, Maziar; Michael Griffin, S
Abstract: Background: Surgery remains the fundamental modality for achieving disease cure in patients with oesophageal adenocarcinoma In those with locally advanced disease, in the UK, is usually used in conjunction with perioperative chemotherapy as per the Magic trial. Not all patients manage to progress to the adjuvant component of the chemotherapy regimen, and its impact on outcome has not been determined. The aim of this review was to compare outcomes in those patients that received neoadjuvant treatment only with those that received neoadjuvant and adjuvant chemotherapy. Methods: A retrospective review of patients who underwent treatment with curative intent for locally advanced oesophageal adenocarcinoma between 2006 to 2016 at a single institution was performed. Outcomes of patients who were staged T3 and above or had evidence of nodal disease and received perioperative chemotherapy were reviewed. Outcomes were stratified according to whether patients received only neoadjuvant chemotherapy or both neoadjuvant and adjuvant chemotherapy. Results: A total of 413 patients underwent transthoracic oesophagectomy and two field lymphadenectomy with perioperative chemotherapy. 276 (67%) received only neoadjuvant chemotherapy, with 137 (33%) receiving at least one cycle of adjuvant chemotherapy. Pathological staging was comparable between groups ( P  = 0.17). Overall estimated median survival was 30 months (neoadjuvant only) Versus 37 months (Both) P  = 0.2. In patients that were found to be node positive median survival was 22 months (neoadjuvant) versus 28 months (both) P  = 0.21. For node negative patients median survival was not reached in both groups. Conclusion: These results indicate a trend towards improved survival with the addition of adjuvant chemotherapy. This may be of greater impact in those patients with nodal involvement. Further studies are required to fully evaluate the impact of adjuvant chemotherapy in patients surgically treated for oesophageal cancer. Disclosure: All authors have declared no conflicts of interest.